2011
DOI: 10.1016/j.cgh.2010.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Smoking as Risk Factors in an Epidemiology Study of Patients With Chronic Pancreatitis

Abstract: Background & Aims Alcohol has been implicated in the development of chronic pancreatitis (CP) in 60%–90% patients, although percentages in the United States are not known. We investigated the frequency of alcohol-related CP at tertiary U.S. referral centers. Methods We studied data from patients with CP (n=539) and controls (n=695) enrolled in the North American Pancreatitis Study-2 from 2000 to 2006 at 20 U.S. referral centers. CP was defined by definitive evidence in imaging or histologic analyses. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
156
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(172 citation statements)
references
References 42 publications
9
156
0
7
Order By: Relevance
“…A study of 540 patients with CP reported "cigarette smoking was an independent, dose-dependent risk factor for CP" [4]. Dose dependent relationships have also been demonstrated between smoking and risk of CP (OR 1.65 >100 cigarettes per lifetime, OR 1.8 current smokers, OR 1.87 >1 pack per day) [27]. The benefits of identifying smokers would mean that smoking cessation interventions could be made to reduce the chance of patients without CP developing it in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 540 patients with CP reported "cigarette smoking was an independent, dose-dependent risk factor for CP" [4]. Dose dependent relationships have also been demonstrated between smoking and risk of CP (OR 1.65 >100 cigarettes per lifetime, OR 1.8 current smokers, OR 1.87 >1 pack per day) [27]. The benefits of identifying smokers would mean that smoking cessation interventions could be made to reduce the chance of patients without CP developing it in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a positive correlation between alcohol abuse and DM occurrence in CP patients (HR, 2.00; 95% CI, 1.43-2.79). Alcoholic cause is the most common etiology of CP in western countries, 28 whereas it constitutes 19% in our singlecenter cohort. As suggested by many previous studies, preexisting asymptomatic pancreatic damage might be amplified and accelerated by alcohol intake, therefore increasing the risk of developing DM in CP.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Dos oito pacientes com pancreatite alcoólica neste estudo, apenas dois foram classificadas como crônica. Sabe-se que aproximadamente 10% das pessoas com pancreatite crônica desenvolvem ataques de pancreatite clinicamente aguda indistinguíveis de outras formas de pancreatite aguda.…”
Section: Evoluçãounclassified